Quantum dots exhibit less bioaccumulation than free cadmium and selenium in the earthworm Eisenia andrei. (15th April 2013) - Stewart, David T.R.; Noguera‐Oviedo, Katia; Lee, Vincent; Banerjee, Sarbajit; Watson, David F.; Aga, Diana S.
Abstract The present study addresses the bioaccumulation behavior of cadmium selenide quantum dots by Eisenia andrei earthworms in a terrestrial environment. Earthworms were exposed to quantum dot‐treated soil for up to 4 wk and analyzed for cadmium and selenium concentration using inductively coupled plasma mass spectrometry. Results were compared with those from earthworms exposed to cadmium nitrate and selenious acid, as positive controls, and those exposed in untreated soil (negative control). Earthworms exposed to quantum dots showed significant bioaccumulation of cadmium and selenium (5.3‐ and 1.5‐fold higher concentration over negative controls, respectively) after 4 wk. Over the same 4 wk, positive control earthworms accumulated 9.2‐ and 2.2‐fold higher cadmium and selenium, respectively, than negative controls for a much more substantial final body burden of the 2 elements. The concentrations also increased with exposure time; cadmium concentrations increased from 3600 ± 310 ng/g to 8080 ± 660 ng/g, from 1 to 4 wk, suggesting that further bioaccumulation may take place with even longer exposure time. The molar ratio of cadmium to selenium in the quantum dot‐exposed worms (6.2) is closer to the ratios seen in positive control worms (7.2) than to the pure quantum dots (1.8), which implies that quantum dots are taken up predominantly in the degraded form. The results suggest that chemical modification of quantum dots to protect them from environmental degradation could potentially reduce bioaccumulation of the nanoparticles by earthworms. Environ Toxicol Chem 2013;32:1288–1294. © 2013 SETAC